ReCoCa Scheme For Wireless Multimedia Sensor Networks (International Journal of Engineering and Computer Science, 2018)
In recent years, rapid growth in low-power circuitry and in cheap complementary metal-oxide semiconductors (CMOS) fosters the growth of a new type of sensor nodes that can retrieve multimedia rich contents such as videos, audio streams, and images along with the ordinary data. These new sensor nodes which were equipped with cameras and microphones are known as multimedia sensors. Wireless multimedia sensor networks (WMSN) have very wide range of applications ranging from environmental monitoring, traffic surveillance and control systems to the healthcare systems and the battel field application. All these applications operate in real time. These applications require information in real time with lesser delay, sensors communicate with each other to provide the required information in lesser time. A region-based co-operative caching (ReCoCa) scheme for WMSN considers each node differently according to the contention introduced by each link. The proposed method selects some notes on the basis of their traffic flow and contention value. A cashing discovery mechanism is proposed which searches the requested data item based on the region. A value based cache replacement method which deletes data items according to the value of the function is also proposed. Simulation results demonstrate the effect of number of notes and Node density in the network over cache overhead and effect of data availability over average delay to serve a request.